Spectrum of pathogenic variants and founder effects in amelogenesis imperfecta associated with MMP20. Issue 5 (6th March 2021) - Nikolopoulos, Georgios; Smith, Claire E. L.; Poulter, James A.; Murillo, Gina; Silva, Sandra; Lamb, Teresa; Berry, Ian R.; Brown, Catriona J.; Day, Peter F.; Soldani, Francesca; Al‐Bahlani, Suhaila; Harris, Sarah A.; et al.
Abstract: Amelogenesis imperfecta (AI) describes a heterogeneous group of developmental enamel defects that typically have Mendelian inheritance. Exome sequencing of 10 families with recessive hypomaturation AI revealed four novel and one known variants in the matrix metallopeptidase 20 ( MMP20 ) gene that were predicted to be pathogenic. MMP20 encodes a protease that cleaves the developing extracellular enamel matrix and is necessary for normal enamel crystal growth during amelogenesis. New homozygous missense changes were shared between four families of Pakistani heritage (c.625G>C; p.(Glu209Gln)) and two of Omani origin (c.710C>A; p.(Ser237Tyr)). In two families of UK origin and one from Costa Rica, affected individuals were homozygous for the previously reported c.954‐2A>T; p.(Ile319Phefs*19) variant. For each of these variants, microsatellite haplotypes appeared to exclude a recent founder effect, but elements of haplotype were conserved, suggesting more distant founding ancestors. New compound heterozygous changes were identified in one family of the European heritage: c.809_811+12delinsCCAG; p.(?) and c.1122A>C; p.(Gln374His). This report further elucidates the mutation spectrum of MMP20 and the probable impact on protein function, confirms a consistent hypomaturation phenotype and shows that mutations in MMP20 are a common cause of autosomal recessive AI in some communities. Abstract : Novel MMP20 variants reveal founder effects via microsatellite genotyping. The effect of these on the stability of the protein was investigated with molecular dynamics simulations.